Modern interactive methodological techniques for working with fiction text (based on the analysis of the ethical dilemma of “good and evil” in the work “Les Misérables” by Victor Hugo) - Bazylova, В.; Token, М.; Mamedova, F. (Karagandy University of the name of academician E.A. Buketov, 2025)
The development of fiction text analysis skills contributes to the formation of communicative, reading, and interpretive competences, which help students grasp the deeper ideas of literary works and enhance their communicative abilities. This article presents modern interactive teaching methods suitable for university instructors of literary disciplines. The issue of developing students’ interpretive skills is particularly relevant in the training of future teachers of Russian language and literature. Such professionals must not only master techniques of literary analysis and interpretation but also be methodologically prepared to teach these skills. There is an objective need to modernize approaches to teaching reading and the literary heritage, particularly that of Victor Hugo, within university curricula. The research results demonstrate that students develop critical thinking and teamwork skills while analyzing philosophical dilemmas such as the conflict between good and evil in literary texts. This article highlights effective methodological techniques and outlines their advantages based on a review of both domestic and international scholarship. It proposes methodological models for analyzing culturally rich passages and defines didactic tasks aimed at encouraging polemical discourse and active student engagement in class. Furthermore, the article identifies ways to enhance teachers’ methodological competence by updating and enriching their instructional toolkit. The findings confirm that these techniques foster interpretive and communicative skills, help students comprehend complex moral ideas and deep philosophical meanings, and promote the development of argumentative discourse. The theoretical conclusions drawn from this study can enrich the methodology of teaching literature, philology, and language culture. The practical significance lies in the development of elective courses and methodological recommendations on foreign literature and teaching methods. The results can be applied in communicatively oriented literature teaching and in the creation of educational resources. By integrating these interactive methodological techniques into educational practice, the goal of updating and expanding the methodological toolkit of literature teachers is effectively achieved.
Көркем мәтінді талдауда заманауи интербелсенді әдістемелік амалдар (Виктор Гюгоның «Аласталғандар» романындағы «адамгершілік пен зұлымдық» дилеммасын талдау негізінде)
Cовременные интерактивные методические приёмы при работе с художественным текстом (на основе анализа этической дилеммы «добра и зла» в произведении «Отверженные» В. Гюго)
Keywords: methodological technique; interactive method; art text; communicative skills; reading competence